(untitled) (Agricultural Engineering, 2017)
The objective of the paper was to verify previously obtained results of research on the impact of the plate diameter on the determined value of pre-compaction stress of soil (NG) with a wider selection of dimensions of samples. Tests were carried out on samples with a diameter (D) of 100 mm and heights (H) of 30, 50 or 100 mm produced from the soil material (M) or collected (NNS) from subsoil with the granulation group of: silt loam, loam, sandy loam, sandy clay loam. The following soil properties were determined: granulation type, density of the solid phase, content of humus and calcium carbonate, reaction, plastic and liquid limit. Properties of samples were described with moisture, dry density of solid particles, porosity of aeration, degree of plasticity and saturation. Samples were loaded with plates of varied diameters. The NG value was calculated with the method of searching for the crossing point of tangents with the secondary stress curve and the virgin stresses curve (a traditional method). It was stated that the plate diameter (d) and sample height (H) do not influence the measurement results when the relation d/D is within 0.5 ≤ d/D ≤ 0.8 and the ratio D/H equals 2. It is possible to omit the condition d/D in a situation when soil is low cohesive and its degree of moisture is ca. 0.41-0.44.